Are White Evangelicals Populists? The View from the 2016 American National Election Study - Guth, James L. (The review of faith & international affairs, 2019)
The role of religion in the rise of populism is sometimes contested, but usually neglected. In this article, we consider the question of whether white American Evangelicals are part of the populist movement. Using the American National Election Study of 2016, we demonstrate that Evangelicals share almost all of the central traits of "populists" posited by observers of such movements and consider some of the implications of this finding.